(untitled) (Applied Biological Research, 2013)
Caseous lymphadenitis is a sporadic bacterial disease of chronic suppurative lymphadenitis in both sheep and goats. The disease is caused by Corynbacterium pseudotuberculosis, a Gram positive rod which generally appears coccoid. The disease is manifested by local inflammation at the site of bacterial entrance, and abscessation of both internal and external lymph nodes (Glen, 2000). Goats are more prone to the external abscesses while sheep are more prone to internal abscesses (Baird and Fontaine, 2007). Internal abscesses are detectable only at necropsy. It is the internal abscesses that are fatal, whereas external abscesses are generally responsible for disease transmission (Ivanovic et al., 2009).